Foot burns: A comparative analysis of diabetic and non-diabetic patients. Issue 3 (May 2021) - Diab, Jason; O'Hara, Justine; Pye, Miranda; Parker, Christine; Maitz, Peter K.M.; Issler-Fisher, Andrea
Highlights: Foot burns although small in area can have significant morbidity affecting function and mobility. Diabetics should be regarded as a high-risk vulnerable group that requires multidisciplinary care. The dangers of a burn injury vary in different seasons for diabetics and non-diabetics impacting clinical outcomes. Peripheral neuropathy is implicated in the presentation and clinical outcome of diabetic foot burns. Abstract: Introduction: Foot burns represent a small part of the body with many challenges. The impact of diabetes on clinical outcomes adds further issues in management that clinicians must consider in their management. These factors have serious implications on morbidity and long term sequelae. Our aim is to analyse epidemiological trends of foot burns and examine the differences between diabetic and non-diabetics at Concord hospital from 2014 to 2019. Methods: A retrospective audit from 2014–19 at Concord General Repatriation Hospital Burns Unit summarised patient demographics, burn injury, diabetic status, operations and length of stay. All foot burn injuries from 2014–19 of all ages and gender that attended Concord burns hospital were included in this study. Results: We treated 797 patients who presented with foot burns, of which 16.2% were diabetic. The average age was higher in diabetics (60.72 years) than non-diabetics (39.72 years) and more males suffered burns compared to females in both groups (p < 0.001). There was a larger portion of elderly patients (greater than 65 years old, 15.1% of total) who sustained foot burns in the diabetic group compared to the non-diabetic group (p < 0.001). The most affected season was summer (27.0%), but diabetic patients were 1.7 times more likely to sustain injury in winter than non-diabetics. Diabetics were 3.8 times more likely to have contact burns compared to non-diabetic patients (p < 0.001). In a multivariable linear regression analysis, factors that contributed to increased length of stay included elderly status, place of event, diabetic status, number of operations, ICU admission, wound infection, amputation, and admission [F (16, 757 = 41.149, p < 0.001, R 2 = 0.465]. Conclusions: With the increase of diabetes, our multidisciplinary approach to diabetic foot care should include nursing, medical and surgical disciplines to identify patients at risk. The data highlights that a focus on prevention and education for diabetes is central to optimize glycaemic control and burn management, whilst providing a multidisciplinary network on discharge.